High-fidelity collisional quantum gates with fermionic atoms - Petar Bojović; Timon Hilker; Si Wang; Johannes Obermeyer; Marnix Barendregt; Dorothee Tell; Thomas Chalopin; Philipp M. Preiss; Immanuel Bloch; Titus Franz (Nature, 2026)
Abstract Quantum simulations of electronic structure and strongly correlated quantum phases are among the most promising applications of quantum computing. These computations benefit from native fermionic encodings 1,2 , enforcing fermionic statistics and conservation laws such as particle number and magnetization 3 independent of gate errors. While ultracold atoms in optical lattices have become established as powerful analogue simulators of strongly correlated fermionic matter 4–7 , neutral-atom platforms have concurrently emerged as versatile, scalable architectures for spin-based digital quantum computation 8 . Unifying these capabilities requires high-fidelity motionally coherent gates for fermionic atoms 9–11 , similar to collisional gates in bosonic systems 12,13 , paving the way for programmable fermionic quantum processors. Here we demonstrate collisional entangling gates with fidelities up to 99.75(6)% and Bell-state lifetimes exceeding 10 s, realized by means of controlled interactions of fermionic atoms in an optical superlattice. Using quantum gas microscopy 14 , we microscopically characterize spin-exchange and pair-tunnelling gates and realize a robust composite pair-exchange gate, a key building block for quantum chemistry simulations 3,15 . Our results establish controlled collisions in optical lattices as a competitive and complementary route to high entangling gate fidelities in neutral-atom quantum computers. Operating intrinsically with fermions, this capability naturally extends to many-qubit architectures, in which fermionic statistics become relevant, enabling complex state preparation and advanced readout 16–19 in scalable analogue–digital hybrid quantum simulators. Combined with local addressing 20,21 , these gates mark a crucial step towards a fully digital fermionic quantum computer based on controlled motion and entanglement of neutral atoms.